Partner-Drug Resistance and Population Substructuring of Artemisinin-Resistant Plasmodium falciparum in Cambodia. (11th July 2017) - Parobek, Christian M.; Parr, Jonathan B.; Brazeau, Nicholas F.; Lon, Chanthap; Chaorattanakawee, Suwanna; Gosi, Panita; Barnett, Eric J.; Norris, Lauren D.; Meshnick, Steven R.; Spring, Michele D.; Lanteri, Charlotte A.; Bailey, Jeffrey A.; et al.
Abstract: Plasmodium falciparum in western Cambodia has developed resistance to artemisinin and its partner drugs, causing frequent treatment failure. Understanding this evolution can inform the deployment of new therapies. We investigated the genetic architecture of 78 falciparum isolates using whole-genome sequencing, correlating results to in vivo and ex vivo drug resistance and exploring the relationship between population structure, demographic history, and partner drug resistance. Principle component analysis, network analysis and demographic inference identified a diverse central population with three clusters of clonally expanding parasite populations, each associated with specific K13 artemisinin resistance alleles and partner drug resistance profiles which were consistent with the sequential deployment of artemisinin combination therapies in the region. One cluster displayed ex vivo piperaquine resistance and mefloquine sensitivity with a high rate of in vivo failure of dihydroartemisinin-piperaquine. Another cluster displayed ex vivo mefloquine resistance and piperaquine sensitivity with high in vivo efficacy of dihydroartemisinin-piperaquine. The final cluster was clonal and displayed intermediate sensitivity to both drugs. Variations in recently described piperaquine resistance markers did not explain the difference in mean IC90 or clinical failures between the high and intermediate piperaquine resistance groups, suggesting additional loci may be involved in resistance. The results highlight an important role for partner drug resistance in shaping the P. falciparum genetic landscape in Southeast Asia and suggest that further work is needed to evaluate for other mutations that drive piperaquine resistance.